Hubungan Kepadatan Hunian dan Kelembaban Ruangan dengan Kejadian Pedikulosis Kapitis. - Rahmita Rahmita; Syamsul Arifin; Lisda Hayatie (Homeostasis, 2019)
Abstract: Pediculosis capitis is an infectious disease of the scalp and hair caused by the infestation of Pediculus humanus var. capitis. The incidence and prevalence of pediculosis capitis is quite high in dense residential environments and humid rooms. The purpose of the study was to determine the relationship between residential density and room humidity with the incidence of pediculosis capitis at Darul Hijrah Islamic Boarding School Martapura. The method used is analytic observational with cross sectional approach. The sample size is 50 people using proportional random sampling technique and variable analysis using Mann Whitney test. The statistical test results for residential density p value = 0.002 and room humidity p value = 0.009. The conclusion of this study there is a relationship between residential density and room humidity with the incidence of pediculosis capitis at girl students in Darul Hijrah Islamic Boarding School Martapura. Keywords: pediculosis capitis, residential density, room humidity. Abstrak: Pedikulosis kapitis adalah penyakit menular pada kulit kepala dan rambut disebabkan infestasi Pediculus humanus var. capitis. Insiden dan prevalensi Pedikulosis kapitis cukup tinggi pada lingkungan padat hunian dan ruangan yang lembab. Tujuan penelitian untuk mengetahui hubungan kepadatan hunian dan kelembaban ruangan dengan kejadian Pedikulosis kapitis di Pesantren Darul Hijrah Puteri Martapura. Metode yang digunakan observasional analitik dengan pendekatan cross sectional. Besar sampel 50 responden dengan teknik pengambilan proportional randon sampling dan analisis variabel dengan uji Mann Whitney. Hasil uji statistik untuk kepadatan hunian nilai p = 0,002 dan kelembaban ruangan nilai p = 0,009. Kesimpulan penelitian ini terdapat hubungan antara kepadatan hunian dan kelembaban ruangan dengan kejadian pedikulosis kapitis pada santriwati di Pesantren Darul Hijrah Martapura. Kata-kata kunci: pedikulosis kapitis, kepadatan hunian, kelembaban ruangan.